Microbial Biotechnology - Patra, Jayanta Kumar ; Vishnuprasad, Chethala N. ; Das, Gitishree (Springer, 2020)
Part I: Application of Microbes in Agriculture. Part II: Application of Microbes for Beneit of Environment…